Integration Profile of Pancasila Students in Problem Based Learning at Elementary School Level - Nurhasanah, Aan; Nugraha, Febby Fajar; Prasetio, Pajar Anugrah; Bekiroglu, Saliha Ozkan (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
This research aims to describe strategies for integrating the values of the Pancasila Student Profile into the Problem Based Learning (PBL) model at the elementary school level. Using the literature review method, this research explores various literature related to the application of the Pancasila Student Profile and the PBL model. The results of the study show that the integration of Pancasila Student Profile values in problem-based learning can be carried out through the PBL Barrows stages or syntax, namely: problem presentation, group organization, data and information collection, hypothesis development, self-directed learning, discussion and evaluation. This strategy involves adapting PBL steps to cover aspects of Pancasila values, so that learning does not only focus on solving academic problems but also on strengthening character and national values. In conclusion, implementing this integration strategy in the PBL model can increase understanding and practice of the values of the Pancasila Student Profile among elementary school students.